1965
DOI: 10.1002/jez.1401590206
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile phase in weaver finch (Ploceus philippinus)

Abstract: The photosensitive weaver bird (Ploceus philippinus) has a long juvenile phase when, while the bird is insensitive to photostimulation, the gonads respond to injected gonadotrophins. It is suggested that the immature status of the hypothalamo/hypophyseal complex may be responsible for the presence of a long pre-photoresponsive phase in this bird.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1972
1972
1988
1988

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…The increase in plasma LH during the development of photosensitivity in natural daylengths was less marked in juvenile than in adult starlings, which suggests that the juvenile hypothalamo-pituitary axis is not able to function at a maximal rate even though the birds become photosensitive. This would be consistent with the suggestion that there is a gradual maturation of the photoperiodic response system in young birds (Thapliyal & Chatterji, 1965;Farner et al, 1983 whereas gradually decreasing and longer 'short' days cause a more gradual development of photo¬ sensitivity (see Farner & Follett, 1966;Hamner, 1968). There is some evidence in the canary that the rate of recovery of photosensitivity is proportional to the length of the short day to which the bird has been exposed (Nicholls & Storey, 1977).…”
Section: Resultssupporting
confidence: 85%
“…The increase in plasma LH during the development of photosensitivity in natural daylengths was less marked in juvenile than in adult starlings, which suggests that the juvenile hypothalamo-pituitary axis is not able to function at a maximal rate even though the birds become photosensitive. This would be consistent with the suggestion that there is a gradual maturation of the photoperiodic response system in young birds (Thapliyal & Chatterji, 1965;Farner et al, 1983 whereas gradually decreasing and longer 'short' days cause a more gradual development of photo¬ sensitivity (see Farner & Follett, 1966;Hamner, 1968). There is some evidence in the canary that the rate of recovery of photosensitivity is proportional to the length of the short day to which the bird has been exposed (Nicholls & Storey, 1977).…”
Section: Resultssupporting
confidence: 85%
“…The mechanism underlying this phenomenon is not known, although several hypotheses have been proposed (e.g. Thapliyal & Chatterji, 1965;Farner & Follett, 1966;Farner et al, 1983;Sharp, 1984). It has been suggested that juveniles may actually be sensitive to photostimulation shortly after hatching, and that this may rapidly switch off the reproductive system, inducing a photorefractory state, but without any overt sign of reproductive activity in terms of gonadal growth (Miller, 1948(Miller, , 1954Farner & Mewaldt, 1955).…”
Section: Introductionmentioning
confidence: 99%